Gender, Investment Financing and Credit Constraints - Ines Pelger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
This paper provides the first evidence on gender differences in investment financing, credit application and credit denial rates in Germany. The empirical analysis is carried out on a sample of firms drawn from the KfW Mittelstandspanel, a representative survey of German SMEs for the period from 2003 to 2009. Our results suggest that in female-owned firms the share of internal capital in investment financing is higher and the share of external funds is lower than for male-owned firms. An analysis of the supply- and demand-side on the credit market shows that women are not more likely to be denied credit but the probability that they apply for credit is on average lower. Yet, this gender difference in the probability of credit application is only evident when considering firms with negative or neutral sales expectations. There is no significant gender difference in credit application rates of firms with positive sales expectations.
urn:nbn:de:bvb:19-epub-12524-4
Keywords: G11; J16; L26; 330; Gender Economics; Female Entrepreneurship; Investment Financing; Investition; Fremdkapital; Eigenkapital; Geschlecht; Kredit; Weibliche Führungskräfte; KMU; Mittelstandsfinanzierung; Schätzung; Deutschland